(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Crime Record Management System is web based application which helps all Police stations across the country and specifically looks into the subject of Crime Records Management. It is well known that Crime Prevention, Detection and Conviction of criminals rely on a highly responsive backbone of Information Management. The efficiency of the police function and the effectiveness with which it tackles crime depend on what quality of information it can derive from its existing records and how fast it can have access to it.